2017
DOI: 10.1016/j.lungcan.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression in advanced NSCLC: Insights into risk stratification and treatment selection from a systematic literature review

Abstract: Tumors can evade immune detection by exploiting inhibitory immune checkpoints such as the programmed cell death-1 (PD-1)/programmed cell death ligand-1 (PD-L1) pathway. Antibodies that block this pathway offer a promising new approach to treatment in advanced/metastatic non-small cell lung cancer (NSCLC). A systematic review of the literature was conducted to assess the association of PD-L1 with important patient and disease characteristics, the prognostic significance of PD-L1 expressing NSCLC tumors, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
206
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(219 citation statements)
references
References 88 publications
(131 reference statements)
7
206
1
5
Order By: Relevance
“…Clinical trials of anti-PD-L1-directed therapy showed that PD-L1 overexpression in cell membranes of NSCLC patients could represent a valid biomarker of response and prognosis . Also, the response to immunotherapy [63,64] in advanced NSCLC patients can be predicted through the study of the tumor microenvironment . Also, a tumoral context dense of CD8+ [65] and FOXP3+ Treg TILs can be considered as predictive marker of response to platinum-based neoadjuvant chemotherapy in advanced NSCLC patients , as well as high levels of the transforming [66,67] growth factor (TGF-) in TILs are predictive of poor post-operative ÎČ ÎČ survival .…”
Section: Tils: Potential Prognostic And/or Predictive Biomarkers In Lmentioning
confidence: 99%
“…Clinical trials of anti-PD-L1-directed therapy showed that PD-L1 overexpression in cell membranes of NSCLC patients could represent a valid biomarker of response and prognosis . Also, the response to immunotherapy [63,64] in advanced NSCLC patients can be predicted through the study of the tumor microenvironment . Also, a tumoral context dense of CD8+ [65] and FOXP3+ Treg TILs can be considered as predictive marker of response to platinum-based neoadjuvant chemotherapy in advanced NSCLC patients , as well as high levels of the transforming [66,67] growth factor (TGF-) in TILs are predictive of poor post-operative ÎČ ÎČ survival .…”
Section: Tils: Potential Prognostic And/or Predictive Biomarkers In Lmentioning
confidence: 99%
“…The recent development of immunotherapy which targets the programmed death‐1/programmed death‐ligand 1 (PD‐L1) axis has been approved for first‐line treatment as well as second‐line treatments of NSCLC in many countries. It alone has significantly improved overall survival (OS) compared with chemotherapy for first‐line NSCLC with PD‐L1 TPS ≄50%, 20%, ≄1% . The higher the PD‐L1 expression, the better the objective response rate and median survival time.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor proportion score (TPS) was counted. TPS >1% was positive and TPS >50% indicated a high expression of PD‐L1 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogenous expression of PD-L1 among the solid tumor group 302 Expression of the PD-L1 checkpoint is a mechanism for immune escape in NSCLC and the 303 percent of cancer cells expressing PD-L1 is used clinically to assess overall PD-L1 expression 304 in tumors (19). In the p-NS tumor group only 3 of 25 tumors had greater than 1% PD-L1 + panCK…”
mentioning
confidence: 99%